Membuat Keputusan yang Melibatkan Analisis Relevant Costing: Suatu Studi Dokumentasi - Dewi, Kartika (Bina Nusantara University, 2011)
In business environment, managers face the challenges to take so many decisions to maximize Net Operating Income for the company as well as company objectives.The decisions taken are involeved with many data:qualitative and quantitative. Because information is many but not all of the are relevant to decision, some are relevant, some are irrelevant. Timing is one of important element in making decision.Manager uses his/her experience in making decision.Â